THE EFFECT OF DISCIPLINE, MOTIVATION, AND ENVIRONMENT ON PERFORMANCE OF EMPLOYEES IN KECAMATAN KOTA PALEMBANG - Muhammad Idris , Choiriyah , Arif Rahman Wijaya (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Problem and research objectives is analyzing the effect of discipline, motivation, and environment together at employee and partially on the performance of Palembang City District Office employees. The plan of this consider could be a correlational plan that communicates the standard relationship between independent variables, individually discipline (X 1 ), motivation (X 2 ), and environment (X 3) on employee with the dependent variable, employee performance (Y). The population used in this study were all State Civil Apparatuses (ASN), SU I, SU II, Plaju, Kertapati, and Jakabaring Districts, amounting to 243 employees. The sample is 151 respondents. Based on the F test the coefficient value sig. F <P-value (?) of 0.05 means that there is a significant relationship between variables of work discipline (X1), work motivation (X2), and work environment (X3), to the dependent variable, namely employee performance (Y). The T-test (t-test) is known that the account for the variables of discipline, motivation and environment partially significant effect on employee performance. The results of the multiple regression equation state that the three coefficients of the positive slant variable are definite, this appears a positive direct relationship (unidirectional) between Work Discipline Variables (X 1 ), Work Motivation (X 2 ) and Work Environment (X 3 ), on the Bound Variable, namely Employee Performance (Y) means work discipline (X 1 ), work motivation (X 2 ) and work environment (X 3 ), the better, the better the performance of employees (Y). This study concludes. First, work discipline, work motivation, and work environment together have a significant effect on employee performance. Second, work discipline, work motivation, and work environment partially have a significant effect on employee performance. Third, work motivation contributes significantly to employee performance (Y), while the lowest work environment has to employee performance (Y) Palembang District Office employees.